2020
DOI: 10.1002/jtr.2397
|View full text |Cite
|
Sign up to set email alerts
|

International travel and political views

Abstract: This research note considers the relationship between international travel experience and one's political views. The findings reveal that those who travel internationally have strongly differentiated views from those who do not, but that these are neither necessarily more liberal nor conservative than those who have not traveled abroad.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Given how we had expected totally opposite results regarding the intersection of Plog's theory and political attitudes, to add credence to our findings we revisited two other recent U.S.‐based research studies we had conducted that had also included both the Plog four‐question scale and one or more political orientation questions – though in neither study had the interplay of the variables been considered. In the first, (Litvin and Smith 2021), with data collected prior to the COVID‐19 crisis, it was found that while party affiliation was relatively evenly split among the Plog segments, when asked to rate President Trump's performance, Allocentrics provided a significantly higher rating than had Psychocentrics. The second study, conducted during the early months of the pandemic (Litvin et al, 2021), as had the present study, found Democrats more likely to be Psychocentric and Republicans more likely to be Allocentric.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given how we had expected totally opposite results regarding the intersection of Plog's theory and political attitudes, to add credence to our findings we revisited two other recent U.S.‐based research studies we had conducted that had also included both the Plog four‐question scale and one or more political orientation questions – though in neither study had the interplay of the variables been considered. In the first, (Litvin and Smith 2021), with data collected prior to the COVID‐19 crisis, it was found that while party affiliation was relatively evenly split among the Plog segments, when asked to rate President Trump's performance, Allocentrics provided a significantly higher rating than had Psychocentrics. The second study, conducted during the early months of the pandemic (Litvin et al, 2021), as had the present study, found Democrats more likely to be Psychocentric and Republicans more likely to be Allocentric.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Scholars have tended to examine the intersection of politics and tourism from a macro‐perspective rather than a micro‐perspective, focusing on topics such as policy rather than on individual tourists. One notable exception is recent research by Litvin and Smith (2021) that compared Americans who had traveled internationally versus those who had not within the preceding 5 years. These authors determined the two groups differed significantly in the opinions they held regarding various political issues, although not in a consistently liberal or conservative direction.…”
Section: Brief Overview Of the Literaturementioning
confidence: 99%
“…Var and Ap (1998) argued that mass tourism seldom generates strong intercultural relationships and reinforces stereotypic images between peoples of different nations, while Nyaupane, Teye, and Paris (2008) found a lack of evidence supporting the notion that travel positively changes one's attitudes. Litvin and Smith (2021) point out that those who travel internationally have strongly differentiated views from those who do not, but that these are neither necessarily more liberal nor conservative than those who have not travelled abroad. Similarly, one more old but relevant seminal research revealed that foreign travel counteracts self-interest, thus leading to a convergence among different points of view (Pool et al 1956).…”
Section: Travelling Abroad Experience and Geopolitical Attitudesmentioning
confidence: 95%
“…Nevertheless, during a few days or weeks of stay in the EU they with very own eyes may become convinced that the horrors of the 'pernicious influences of European culture' are just fabrications of Russian propaganda. Similar to the other global contexts, tourist trips to the EU may stipulate Ukrainians to be more open-minded, to be more tolerant to the Western culture in general or a specific European national culture in particular, to enhance cross-cultural understanding and to dispel pre-shaped stereotypes (Yu & Lee 2014;Aleshinloye et al 2020;Litvin & Smith 2021).…”
Section: Background Of Travelling Abroad and Pro-european Attitudesmentioning
confidence: 99%
“…However, whereas significant literature has examined the politics of tourism from the perspective of tourism policy, only very limited research has examined the relationship between individuals’ political attitudes and their travel behaviors. In the limited extant literature, Litvin and Smith (2021a , 2021b ) found that American international travelers differed from their non-international traveling counterparts with regards to their attitudes toward numerous political issues. However, these differences did not exhibit a consistently liberal or conservative tendency.…”
Section: Background—a Review Of Relevant Literaturementioning
confidence: 99%